Comparative analysis of jaw morphology and temporomandibular disorders: A three-dimension imaging study. Issue 3 (3rd May 2020) - Colonna, Anna; Manfredini, Daniele; Lombardo, Luca; Muscatello, Luca; Marchese-Ragona, Rosario; Arveda, Niki; Siciliani, Giuseppe
ABSTRACT: Objective : To investigate the association between volumetric measurements of craniofacial morphology and temporomandibular disorders (TMDs). Methods : Computerized tomography (CT) scans of 20 individuals aged 18 to 40 with (TMD group) or without TMJ pain (control group) were gathered based on a case-control design. Three-dimensional reconstructions were performed to evaluate the gonial angle, condylar volume, and the distance between the posterior edge of the condyle and the sigmoid notch. Results : The gonial angle was significantly larger (8% difference) in the TMD group with respect to controls, whereas the condylar volume was significantly higher in the control group (15.2% difference). No significant difference was found in the linear distance. Conclusion : There is an association between the presence of TMJ pain and some features of craniofacial morphology. Individuals with TMJ pain have a lower condylar volume and a tendency towards hyperdivergent growth.